THE ROLE OF DIGITAL LEARNING IN IMPROVING STUDENTS' UNDERSTANDING OF ISLAMIC RELIGIOUS EDUCATION MATERIALS: TEACHER AND STUDENT PERSPECTIVES - Barokah, Miftahul; Pradani, Rizki Febri Eka; Lama, Alma Vorfi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Digital learning has become an effective alternative for improving students' understanding of Islamic Religious Education (PAI) material. This study aims to explore the role of digital learning in improving students' understanding of PAI material at SMP Negeri 9 Kota Probolinggo by looking at the perspectives of teachers and students. The approach used in this study is qualitative with a case study design. Data were collected through in-depth interviews, participatory observations, and documentation involving PAI teachers and students as respondents. Data analysis was carried out using thematic analysis techniques. The results of the study showed that digital learning positively impacts students' understanding, especially in terms of ease of accessing materials and increasing student engagement through digital applications and platforms such as Google Classroom and learning videos. Students feel more motivated and can repeat the material according to their needs. However, the challenges faced include limited direct interaction between teachers and students, technical problems such as unstable internet connections, and the difficulty some students need help accessing adequate technology. This study concludes that although digital learning can improve students' understanding of PAI material, factors such as access to technology, teacher training, and more intensive interaction must be considered so that digital learning can be more effective. Recommendations for further development include increasing internet access and teacher training in learning technology. With these steps, digital learning can be utilized optimally in improving the quality of religious education in schools.